2011
DOI: 10.1038/onc.2010.626
|View full text |Cite
|
Sign up to set email alerts
|

PI3K inhibition results in enhanced HER signaling and acquired ERK dependency in HER2-overexpressing breast cancer

Abstract: There is a strong rationale to therapeutically target the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway in breast cancer since it is highly deregulated in this disease and it also mediates resistance to anti-HER2 therapies. However, initial studies with rapalogs, allosteric inhibitors of mTORC1, have resulted in limited clinical efficacy probably due to the release of a negative regulatory feedback loop that triggers AKT and ERK signaling. Since activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
401
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(452 citation statements)
references
References 54 publications
47
401
3
1
Order By: Relevance
“…6B). This supports the observations of Serra and colleagues where PI3K inhibition in ERBB2-overexpressing cells was compensated for by ERK/MAPK dependence (30). We also examined other kinases downstream of the MET and ERBB2 receptors using a phospho-kinase antibody array of 42 kinases, but observed no differences in their activity.…”
Section: Egfr and Erbb3 Do Notsupporting
confidence: 90%
“…6B). This supports the observations of Serra and colleagues where PI3K inhibition in ERBB2-overexpressing cells was compensated for by ERK/MAPK dependence (30). We also examined other kinases downstream of the MET and ERBB2 receptors using a phospho-kinase antibody array of 42 kinases, but observed no differences in their activity.…”
Section: Egfr and Erbb3 Do Notsupporting
confidence: 90%
“…This model also revealed that the lack of R-Ras2 promotes signalling compensation mechanisms in tumours similar to those seen before on the inactivation of specific PI3K/mTORC route signalling elements [39][40][41][42][43][44][45] . In those cases, such compensation effects are mostly mediated by the elimination of mTORCdependent negative feedbacks on the Raf/Erk route [39][40][41][42][43][44][45] . However, the development of these signatures in MMTVHer2 tg ;Rras2 À / À mice seems to require long-term Darwinian selection events, because primary MECs from both MMTVHer2 tg ;Rras2 À / À (this work) and Rras2 À / À knockout mice 18 do not exhibit such signatures.…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismssupporting
confidence: 72%
“…Despite this, the R-Ras2-dependent PI3Ka pool is clearly relevant in vivo, given the marked tumorigenic and metastatic defects shown by R-Ras2-deficient breast cancer cells when implanted in recipient mice. The morphogenetic alterations seen in preneoplasic mammary glands of MMTV-Her2 tg ;Rras2 À / À mice, together with the signalling compensation events detected in tumours arising in those mice, are also indirect evidence in favour of defects in the PI3Ka/Akt/ mTORC route in this experimental model 30,31,[39][40][41][42][43][44][45] . However, as reconstitution experiments are not possible in this case, we cannot formally exclude the possibility that those events could be generated by defects in other R-Ras2-dependent signalling routes (Supplementary Discussion).…”
Section: R-ras2 Deficient Tumours Develop Compensatory Mechanismsmentioning
confidence: 64%
“…These gain-of-function mutations in the PI3KCA gene are found in a broad range of cancers, and they are highly enriched in breast cancer, where they are observed in 20-25% of cases (7). In addition, breast cancers with amplified HER2, which comprise ∼20% of all breast cancers, (8) are also particularly sensitive to PI3K inhibition (9)(10)(11). However, even among patients whose cancers harbor PIK3CA mutations, a significant heterogeneity of responses has been observed to PI3K inhibitors currently being tested in clinical studies (3)(4)(5).…”
mentioning
confidence: 99%